Cultural Values' Integration in Character Development in Elementary Schools: The Sukuraga as Learning Media - Nurasiah, Iis; Sumantri, Mohamad Syarif; Nurhasanah, Nina; Casmana, Asep Rudi (Frontiers in Education, 2022)
The purpose of this study was to analyze the character development of students through the use of the Puppet Sukuraga application. The facts on the ground about learning during a pandemic in fulfilling the affective dimension tend to be ignored, teachers emphasize the cognitive dimension more. In the affective dimension, Puppet Sukuraga is used as a character education media in the form of applications that can develop students' character moreover, this puppet can be used on mobile phones or laptops so that it supports online and offline learning and Info, anyone who uses it knows the Sukuraga wayang in depth. This study uses a qualitative method conducted in one of the elementary schools in Indonesia that already uses the Puppet Sukuraga application. The number of subjects in this study were 2 teachers and 18 students in grade 2. Data is provided in the form of a detailed description of the subject's activities from the subject's perspective through interviews and group discussion forums. In-depth interviews were given to teachers and students, conducted 45 minutes before and after learning in class. The results of the study show that the use of the Sukuraga wayang application can develop students' character, especially in the character of tolerance and responsibility. Students' tolerance is more developed, as can be seen from the attitude of respect for differences in religion, ethnicity, habits, and differences of opinions. The character of responsibility is also more developed such as being responsible for their duties in doing homework, being responsible for carrying out the teacher's orders, and being responsible for maintaining his five senses by carrying out useful activities. This research has implications for elementary school teachers in Indonesia during the limited online and face-to-face learning period.